12/14/14‐Helix Formation in 2:1 α/β‐Hybrid Peptides Containing Bicyclo[2.2.2]octane Ring Constraints. Issue 34 (14th July 2016) - Legrand, Baptiste; André, Christophe; Moulat, Laure; Didierjean, Claude; Hermet, Patrick; Bantignies, Jean‐Louis; Martinez, Jean; Amblard, Muriel; Calmès, Monique
Abstract: The highly constrained β‐amino acid ABOC induces different types of helices in β urea and 1:1 α/β amide oligomers. The latter can adopt 11/9‐ and 18/16‐helical folds depending on the chain length in solution. Short peptides alternating proteinogenic α‐amino acids and ABOC in a 2:1 α/β repeat pattern adopted an unprecedented and stable 12/14/14‐helix. The structure was established through extensive NMR, molecular dynamics, and IR studies. While the 1:1 α‐AA/ABOC helices diverged from the canonical α‐helix, the helix formed by the 9‐mer 2:1 α/β‐peptide allowed the projection of the α‐amino acid side chains in a spatial arrangement according to the α‐helix. Such a finding constitutes an important step toward the conception of functional tools that use the ABOC residue as a potent helix inducer for biological applications. Abstract : Let's do the twist : α/β‐Hybrid peptides combining a 2:1 α/β pattern of the highly constrained ABOC residue and proteogenic α‐amino acids adopted an unprecedented 12/14/14‐helix in solution. No helical polymorphism was observed for this helix. The 9‐mer 2:1 α/β peptide showed some similarities in α‐AA side‐chain projection with that of an α‐helix.